Potassium metabolism in patients with rheumatoid arthritis. Effects of treatment with depot tetracosactrin, spironolactone, and oral supplements of potassium chloride. Issue 6 (December 1975) - Nuki, G; Boddy, K; Kennedy, A C; King, P; Duncan, A M; Buchanan, W W
Abstract : (1) Plasma and urine electrolytes and whole body potassium have measured before and after a 2-week administration of depot tetracosactrin 0.5 mg on alternate days to eight patients with rheumatoid arthritis (RA.) The effects of adding supplements of potassium chloride (48 mmol/d) and spironolactone 200 mg daily have been investigated. (2) Acute changes in red blood cell water and potassium content, plasma electrolyte concentration, and plasma 11-hydroxycorticosteroid levels were measured for 48 hours after a single intramuscular injection of 0.5 mg depot tetracosactrin in six patients with RA. (3) The measured total body potassium was significantly less than that predicted from the height, weight, and age formula in patients with RA. (4) Treatment with depot tetracosactrin resulted in an acute fall in plasma and red cell potassium independent of external potassium loss. (5) Two weeks of treatment with depot tetracosactrin resulted in hypokalaemia and a rise in plasma sodium and bicarbonate. There was no associated electrocardiogram changes or a rise in blood pressure. (6) Neither oral potassium supplements nor spironolactone altered total body potassium. (7) The significance of the findings and the physiological mechanisms underlying them are discussed.